Ginsenoside Compound K Regulates HIF-1α-Mediated Glycolysis Through Bclaf1 to Inhibit the Proliferation of Human Liver Cancer Cells - Zhang, Silin; Zhang, Meilan; Chen, Jiaxin; Zhao, Jiaqi; Su, Jielin; Zhang, Xuewu (Frontiers in Pharmacology, 2020)
This study aimed to demonstrate that ginsenoside compound K (20 (S)-ginsenoside CK; CK) downregulates Bcl-2-associated transcription factor 1 (Bclaf1), which inhibits the hypoxia-inducible factor-1α (HIF-1α)-mediated glycolysis pathway to inhibit the proliferation of liver cancer cells. Treatment of hypoxic hepatoma cells (Bel-7404 and Huh7) with different concentrations of CK showed that CK inhibited the proliferation of hepatoma cells in a time- and concentration-dependent manner; furthermore, the ability of the cells to form colonies was reduced, and cell growth was blocked in the G0/G1 phase. CK regulation of the expression of HIF-1α and HIF-1α ubiquitination-related proteins in liver cancer cells promoted the degradation of HIF-1α ubiquitination; moreover, it reduced the activity of key enzymes involved in glycolysis, the pressure of cellular glycolysis, and the rate of real-time ATP production, thereby inhibiting the glycolysis pathway. It also decreased the expression of Bclaf1 in hypoxic liver cancer cells and thus reduced the ability of Bclaf1 to bind to HIF-1α. CRISPR/Cas9 technology was used to knock out the Bclaf1 gene in hypoxic Bel-7404 and Huh7 cells; in these cells, CK further suppressed the expression of HIF-1α, promoted HIF-1α ubiquitination, and inhibited the glycolysis pathway. In a rat model of primary liver cancer induced by diethylnitrosamine, positron emission tomography and computed tomography scans showed that after CK administration, tumor tissue volumes were reduced and glucose uptake capacity decreased. Increased Bclaf1 and HIF-1α expression promoted the ubiquitination of HIF-1α and inhibited the glycolysis pathway, thereby inhibiting the proliferation of liver cancer cells. In summary, this study confirmed by in vitro and in vivo experiments that CK downregulates the expression of Bclaf1 in hypoxic liver cancer cells, inhibits the HIF-1α-mediated glycolysis pathway, and inhibits cell proliferation, suggesting that targeting Bclaf1 with CK has potential as a therapy for liver cancer patients.